Penerapan Metode Topsis Untuk Menentukan Buku Favorit Dalam Pengadaan Buku Perpustakaan - Habsyi Ikhlashul Ariq; Adiat Pariddudin (Universitas Binaniaga Indonesia, 2023)
The procuring books is one of the jobs of a librarian both in the university library and the public library, the procurement of books itself has several stages and one of them is determining the priority books to provide and also recommendations for additional books or other supports. In one of the libraries in the city of Bogor, they still have problems in determining the title of the book to be held because the way of work and the assessment process that is still carried out is still conventional and repetitive, therefore in this study, a Decision Support System was created that can determine the title of the book. priority in procurement. The method used is the TOPSIS method. The results of the calculation of the Topsis method are in the form of a ranking using book titles as an alternative, as well as several special criteria used and approved by the relevant Libraries such as Book Availability, Types of Books, and also the Number of Borrowers. This research was conducted to make it easier for library staff and also to increase the effectiveness of determining the priority book titles in one count of an application. To improve the recommendations given by the TOPSIS method, a test was carried out using the Rank Spearmen Correlation, the test results obtained were 0.96, these results were in the